2022
DOI: 10.3389/fimmu.2022.884648
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-Induced Memory-Like NK Cells: From the Basics to Clinical Applications

Abstract: Natural killer (NK) cells are lymphocytes with a key role in the defense against viral infections and tumor cells. Although NK cells are classified as innate lymphoid cells (ILCs), under certain circumstances they exhibit adaptive and memory-like features. The latter may be achieved, among others, by a brief stimulation with interleukin (IL)-12, IL-15 and IL-18. These cytokine-induced memory-like (CIML) NK cells resemble the trained immunity observed in myeloid cells. CIML NK cells undergo transcriptional, epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 86 publications
0
33
0
Order By: Relevance
“…Interestingly, this study was followed by an in-human study which showed that allogeneic human CIML NK cells were able to proliferate in patients with AML and improved clinical outcomes. 175 These promising results have led to several subsequent CIML NK cell clinical trials in AML patients (extensively reviewed in 176,177 ), which have shown promising results and led to more innovative strategies such as the use of CIML NK cells in combination with chimeric antigen receptor (CAR) technology. Thus, if we manage to better understand the epigenetic and metabolic reprogramming necessary for NK cell survival and effector activity in a pro-inflammatory environment, we can further develop pioneering off-the-shelf NK cell-based therapies in both prophylactic as well as in therapeutic settings and turn fundamental research into applicable solutions for patients.…”
Section: Epi G Ene Ti C Reg Ul Ati On Of Nk Cell Survival During Infl...mentioning
confidence: 99%
“…Interestingly, this study was followed by an in-human study which showed that allogeneic human CIML NK cells were able to proliferate in patients with AML and improved clinical outcomes. 175 These promising results have led to several subsequent CIML NK cell clinical trials in AML patients (extensively reviewed in 176,177 ), which have shown promising results and led to more innovative strategies such as the use of CIML NK cells in combination with chimeric antigen receptor (CAR) technology. Thus, if we manage to better understand the epigenetic and metabolic reprogramming necessary for NK cell survival and effector activity in a pro-inflammatory environment, we can further develop pioneering off-the-shelf NK cell-based therapies in both prophylactic as well as in therapeutic settings and turn fundamental research into applicable solutions for patients.…”
Section: Epi G Ene Ti C Reg Ul Ati On Of Nk Cell Survival During Infl...mentioning
confidence: 99%
“…Due to their high cytotoxic activity and anti-tumor properties, cytokine-induced NK cells represent the novel immune cell therapy against tumors. However, their therapeutic potential may be further improved studying how they change after cytokine exposure, combination immunotherapy approaches, genetically modifications ( 81 ). Generally, the anti-tumor activity of NK cells is based on the responsiveness to growth factors and cytokines that can extremely influence the tumor immune surveillance.…”
Section: Regulation Of Nk Activitymentioning
confidence: 99%
“…Romee and colleagues pre-activating ex vivo allogeneic NK cells with a mixture of cytokines, including IL-12, IL-15, and IL-18, characterized the so-called “cytokine induced memory-like NK cells” (CIML-NK), which show enhanced proliferation capability, high IFN-γ production, high cytotoxicity, and, after a second encounter with tumor targets, an enhanced recall response [ 173 , 174 ]. CIML-NK cells appear as a promising NK cell therapy and clinical trials evaluating the use of CIML-NK for refractory/relapsed AML patients showed encouraging results, prompting the design of clinical trials evaluating the use of CIML-NK in solid tumors [ 175 ]. Moreover, the CIML-NK platform could be further combined with other immune-mediated strategies, such as CAR engineering.…”
Section: Future Perspectivesmentioning
confidence: 99%